Use of Mathematical–Statistical Methods for Evaluating Data from Chemical Analysis Referring to the State of the Environment - Paksy, L.; Lengyel, A.; Bánhidi, O. (Microchemical journal, 1998)
The necessity for using appropriate evaluation methods in environmental chemical analysis is demonstrated in examples from the River Sajó and the urban air of Miskolc. River Sajó is a natural ecosystem, whereas the city of Miskolc is an artificial environment. Chemical analysis was performed on River Sajó water at regular, weekly intervals to determine the following inorganic components: Na, Mg, Si, P, K, Ca, Cr, Fe, Co, Ni, Cu, Zn, As, Sr, Cd, Ba, Pb. The behavior of the assumed natural and polluting components was studied, characterizing them by their distribution, trend, occurrence of outliers and cross-correlation. Similarly, some polluting components of the urban air of Miskolc were studied, and characteristic features of the changes were observed. Because of the rapidly changing distributions and frequently occurring trend, nonparametric methods can be recommended for evaluation and forecasting.